IJIMAI Editor's Note - Vol. 3 Issue 1 - Ruben Gonzalez Crespo (International Journal of Interactive Multimedia and Artificial Intelligence, 2014)
The research works presented in this issue are based on various topics of interest, among which are included: bayesian networks, evolutionary algorithms, virtual reality, web advertising, 3D technologies, traffic expression, Smart Cities, computational sustainability, computer vision, image recognition, deep neural networks, graphical models, mobile devices, human/complex system interactions, multi-agent systems, Physics inspired behaviours, etc.